Frequency of Septal Perforation in Sub-Mucous Resection of Nasal Septum - Allah Noor, Khalil Ahmed Orakzai, Azam Khan, Mamoor Khan, Sohail Khan, Mubassir Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: In this study, the efficacy of sub-mucous resection (SMR) in the management of patients presented with deviated nasal septum (DNS) was assessed with particular emphasis on the post-operative septal perforation. Methods: A descriptive study was carried out for six months (i.e., from October 2021 to March 2022) at the Ear, Nose and Throat (ENT) Department of Hayatabad Medical Complex, Peshawar, Pakistan. Results: A total of 203 patients who presented with DNS were included herein, where the male to female ratio was 1.39:1 while the mean age was 30 ±3.74 (range= 20-60) years. The majority patients presented with S type DNS (80; 39%), followed by C type DNS (75, 37%) while the spur type DNS was seen in only 48 (24%) cases. After SMR, 08 (4%) cases of septal perforation were observed with anterior rhinoscopy. Conclusions: These results demonstrate the fact that post-surgical septal perforation is a critical clinical complication.